2016
DOI: 10.2147/ndt.s104260
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and parental styles assessed by adolescents suffering from inflammatory bowel diseases and their parents

Abstract: Background Inflammatory bowel diseases (IBDs) in adolescents are chronic medical conditions with a substantial influence on the quality of life (QoL) of the families. Methods A total of 27 adolescents suffering from IBD, 39 healthy adolescents, and their parents were included in the cross-sectional study. The adolescents completed the questionnaires ADOR (parenting styles), KidScreen-10 (QoL), SAD (The Scale of Anxiety in Children), and CDI (Children’s Depression Invent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 26 publications
0
25
0
1
Order By: Relevance
“…Warm and accepting parent-adolescent relationships contributed to the well-being of children and adolescents at risk [ 20 ], and were related to higher levels of QOL and fewer psychological symptoms in adolescents with chronic diseases [ 21 ]. Also, The QOL of adolescents suffering from inflammatory bowel disease positively correlated with the warm parental style [ 22 ] while the QOL of adolescents with diabetes type 1 was positively associated with mindful parental style [ 23 ]. Our findings indicate that emotional warmth is positively associated with the HRQOL of adolescents with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Warm and accepting parent-adolescent relationships contributed to the well-being of children and adolescents at risk [ 20 ], and were related to higher levels of QOL and fewer psychological symptoms in adolescents with chronic diseases [ 21 ]. Also, The QOL of adolescents suffering from inflammatory bowel disease positively correlated with the warm parental style [ 22 ] while the QOL of adolescents with diabetes type 1 was positively associated with mindful parental style [ 23 ]. Our findings indicate that emotional warmth is positively associated with the HRQOL of adolescents with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, distinctions between maternal and paternal psychosocial functioning have been examined in prior research, which allows for a more in-depth analysis of prevalence compared to norms. Fairly consistently across studies, mothers of youth with IBD report higher levels of psychological distress symptoms in comparison to healthy controls and normative samples [ 30 , 31 , 32 ]. In a study conducted with Swedish families of children with IBD, the domains of somatization, interpersonal sensitivity (i.e., feeling self-conscious or uncomfortable in interpersonal situations), depression, and anxiety on the Symptom Checklist 90 (SCL-90) were significantly elevated when compared to mothers of children without IBD [ 30 ].…”
Section: Parent Psychosocial Functioningmentioning
confidence: 96%
“…In a different sample, Swiss mothers reported significantly higher symptoms of dysthymia and social phobia, as well as a higher overall symptom score compared to population norms on the short-form of the SCL-90 [ 32 ]. In a study conducted in the Czech Republic, mothers of youth with IBD reported moderate levels of anxiety as measured by the Beck Anxiety Inventory and endorsed significantly more symptoms of anxiety than mothers of healthy children [ 31 ]. However, there was no significant difference in symptoms of depression between mothers in the illness and control group in this sample [ 31 ].…”
Section: Parent Psychosocial Functioningmentioning
confidence: 99%
See 2 more Smart Citations